Research A Problem of The Concept "Foreign Language Inclusions" In Linguistics (Texas Journal of Philology, Culture and History, 2023)
In this article, we have analyzed, interpreted and classified foreign language inclusions. Introduced with the research and hypothesis of several scientists in this field. Presented divisions and subdivisions of foreign language inclusions done by linguists and gave examples according to their classifications.